I am having trouble proving that the following are linear transformation: 1) T:R^3---> R^2 is an L.T defined by T(a1,a2,a3)= (a1-a2,2a3) 2)T:P2(R)--->R^3be a linear transformation defined by T(a0+a1x+a2x^2)=(a0,a1,a2) thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by JCIR I am having trouble proving that the following are linear transformation: 1) T:R^3---> R^2 is an L.T defined by T(a1,a2,a3)= (a1-a2,2a3) thanks just do it by definition.. you can easily do the second one..
View Tag Cloud